Effects of high voltage electrical stimulation on the rate of pH decline, meat quality and colour stability in chilled beef carcasses (Bangladesh Veterinarian, 2013)
Fifty beef carcasses were used to determine the effects of High Voltage Electrical Stimulation (HVES, 800 Volts) on pH and meat quality. Meat from M. longissimus dorsi was examined for pH and temperature at 1, 2, 5, 10 and 24 hours, while tenderness and colour were examined seven days after slaughter. HVES decreased the pH of the meat and accelerated rigor mortis (P